Describing the people that contribute to an emergency centre crowd at Khayelisha Hospital, Western Cape, South Africa - Ahiable, Emmanuel Kwadzo (Division of Emergency Medicine, 2017)
Background: The emergency centre (EC) is a vibrant and challenging environment from both an operational and clinical perspective. Emergency centre crowding has been referred to as one of the biggest challenges confronting policy-makers, emergency healthcare professionals (including physicians and nursing staff) and their patients globally. Elsewhere, EC crowding has been thoroughly studied. Resource restrictions render more detailed flow studies less achievable locally. Anecdotally, our local ECs are perceived to be fairly crowded. This study aimed to describe the EC crowd at Khayelitsha hospital by establishing the number and different categories of people at predefined times during the day over a four week period. Method: A prospective, cross-sectional, design was used. Headcounts were made by predefined groups at 09:00, 14:00 and 21:00 every day for four weeks. Predefined groups included doctors, nurses, visitors, patients, and other allied health staff. Summary statistics were used to describe the data and precision were described using the 95% confidence interval. Results: There were 37, 34 and 27 different people categories found in the EC during the three different shifts respectively. A total of 16353 people were counted during the study period. On average 6370 (39%) of the groups were staff, 5231 (32%) were patients and 4752 (29%) were visitors. Of the staff, 1488 (9%) were EC nurses, 733 (4.4%) were non-EC doctors, 586 (3.6%) were EC doctors, and 445 (3%) were non-EC nurses. The EC was consistently crowded – average occupancy: 130%. Notably, Mondays had the highest occupancy of 144% and Sundays had the lowest of 130%. Conclusion: Describing the people categories that contribute to the EC crowd in a low-to-middle income setting may provide a uniform template in defining EC crowding. In our study, we can conclude that the main findings were: Staff levels fluctuated predictably with less staff at night and over weekends whilst patients remained constant. Non-EC doctors more than doubled during the day on week shifts, in significantly more numbers than EC doctors, suggesting that many of the patients in the EC were likely to be admissions without a place to be admitted to. Although clinical staff numbers did not reduce during the busiest visitor times (afternoons), given the huge amount of crowding at this time care was likely to suffer. Further research is recommended to describe the findings in more detail including some of the limitations mentioned in this thesis.